The Shear Strength and Dilatancy Behavior of Wheat Stored in Silos - Changnv Zeng; Yuke Wang (Complexity)
This paper focuses on the shear and dilatancy behavior of wheat stored in silos with various densities and normal stresses. The goal is to find a quantitative relationship modeling the peak friction angle and maximum dilatancy angle of wheat stored in silos. A total of 48 direct shear tests were carried out to research the evolution of shear and dilatancy of stored wheat in silos. It is revealed that strength of wheat in bulk attributes to the combination of frictional and dilatant during shearing, in particular attributing to its elliptic shape. An increase in relative density enhances the peak friction angle as well as the dilation. The relationships between relative density, peak friction angle, and dilatancy angle were presented based on the tests data and Bolton’s theory. Then an advanced model is developed to evaluate the peak shear behavior of wheat stored in silos considering the dilatancy of the stored wheat. It is a practical method to predict the strength and dilatancy behavior of wheat stored in silos.